Furfuryl resin/CNT/carbon fiber drilling, using carbide drill coated with Balinit-Helica - David-Müzel, Sarah [UNESP]; Bonhin, Eduardo Pires [UNESP]; Ribeiro, Marcos Valério [UNESP]; Botelho, Edson Cocchieri [UNESP]; Alves, Manoel Cléber de Sampaio [UNESP] (Taylor & Francis, 2020)
Bolted joints are the most common form of union of the components in an airplane, with drilling being the most used process in obtaining the holes. However, this process can cause several defects, so the parts produced can go to the assembly line with some defects. Aim of this manuscript was to analyze the influence of spindle speed and the feed in the power consumption and system vibration, during the drilling process of the composite of furfuryl resin/Carbon Nanotube/Carbon fiber, as well as the quality of the hole, the dimensional error, and the tool wear. Spindle speed of 1000 and 2000 rpm and feeds of 0.025, 0.05, 0.1, 0.2 and 0.3 mm/rev were used. The drills used are carbide coated with Balinit Helica®, 6.5 mm in diameter. Concluded that the feed influences on the power, vibration and in the quality of the holes. The addition of nanotubes does not inhibit dimensional error but causes it to be smaller. Helica coating is not ideal for drilling composites reinforced with carbon fiber.
Keywords: aerospace; bio resin; Composite; dimensional error; machining; nanocomposite; power; vibration; wear